PENGARUH AKUPRESUR DALAM MEMINIMALISIR DISMINORE PRIMER PADA REMAJA PUTRI DI JURUSAN KEPERAWATAN POLTEKKES KEMENKES MATARAM TAHUN 2013 - ., Mardiatun (Jurnal Health and Sport, 2013)
Primary Dysmenorhea is menstruation pain that its not because of pathology but there is over prostaglandin in menstruation blood so its make hyperactivity uterus. One of therapy non farmakologi that could be their alternatif is acupressure therapy because this therapy have many of advantage, one of them is not have any side effect. The purpose of this experiment is to know the efectivity of acupressure therapy to minimize primary dys-menorhea of girls. This experiment uses quasy experiment by using one group pre-test and post-test. The sample in this experiment is use one group that contain 9 girls whom suffering primary dysmenorhea. The pain intensity of each subject is measured before and after therapy, then the different of them is measured to know the efectivity of acupressure therapy. By using sample-paired t-test, the result of this research is p (0.00) < 0,05 so there is significant differences between before and after therapy and Ho is reject and H1 is accepted. The conclution is acupressure therapy effective to minimize primary dysmenorhea of gilrs.